Exploring Hydrographical Structures in the Cape Verde Frontal Zone through in Situ Data and Numerical Modelling during Fluxes-II Survey - Hernández García, Inés; Machín Jiménez, Francisco José; Coca Sáez De Albéniz, J. (2020)
The Cape Verde Frontal Zone (CVFZ) is a dynamically complex region located at the eastern North Atlantic Subtropical Gyre (20ºW to 30ºW, ~20ºN), where the warmer and more saline North Atlantic Central Water (NACW) and the colder and less saline South Atlantic Central Water (SACW) interact. It is defined by the intersection of the 36.0 isohaline with the 150 m depth isobath. The CVFZ presents high variability due to the presence of lateral intrusions, filaments from the upwelling system, and mesoscale and submesoscale eddy fields with sharp thermohaline gradients. Temperature and salinity decrease with depth, which compensates their effect on density and makes the front dynamically stable in the vertical direction. This project aims to analyse the features at the CVFZ during November 2017 FLUXES-II cruise using the in situ data from ship CTD stations, a SeaSoar, and two underwater gliders with biochemical and dynamical instruments. The variables used on this study were potential temperature, practical salinity, potential density, and oxygen concentration. Outputs from the Copernicus Mercator model were compared with in situ data to determine the model skill on reproducing the mesoscale and submesoscale features. Wavelet analyses were conducted to compare the spatial scales of variability that can be resolved with the sampling methods. Results showed that the ship CTD data reaches the greatest depth of all the sampling methods, and the SeaSoar is the fastest method. The glider and the SeaSoar capture the smallest scales and show the frontal features with greater detail, while the glider has a slightly better resolution. The surface layer showed the highest variability. The main features found were intrusions of SACW into the NACW. It was found a tilted lateral intrusion, located at slightly greater depths than the other intrusions, that might be due to the deformation of a previously existing intrusion.